Financing the Low-Carbon City: Can Local Government Leverage Public Finance to Facilitate Equitable Decarbonisation?. Issue 1 (2nd January 2019) - Hadfield, Paris; Cook, Nicole
Abstract: As decarbonisation interventions proliferate within cities, local governments setting ambitious targets are increasingly engaged in complex financial relations. Recognising the necessary cost of renewable and energy efficient infrastructures, and the ever-present constraints on public funds, this paper argues that finance is a critical node through which local governments advance decarbonisation in urban localities. While local decarbonisation strategies have been viewed cautiously for their potential to overburden individuals at the expense of more systematic and organisational change, this paper reveals a more complex picture. Drawing on decarbonisation initiatives in two Melbourne municipalities—Moreland and Darebin—it identifies four ways in which local governments are using public finance to achieve their sustainability objectives. Local governments are brokering bulk product purchases for residents; lending upfront capital for solar PV via local property taxes; purchasing energy efficient products and funding innovative technology pilots; and procuring renewable energy supply through multi-stakeholder power purchase agreements. By targeting lower income households and pooling resources with other organisations, the paper shows that local governments can address socio-economic inequality and facilitate extra-local change towards a low-carbon city. However, these incremental achievements emphasise the need for co-ordination and state engagement to realise decarbonisation at a meaningful scale.